Women's decision-making processes and the influences on their mode of birth following a previous caesarean section in Taiwan: a qualitative study - Shu-Wen Chen; Alison M. Hutchinson; Cate Nagle; Tracey K. Bucknall (BMC, 2018)
Abstract Background Vaginal birth after caesarean (VBAC) is an alternative option for women who have had a previous caesarean section (CS); however, uptake is limited because of concern about the risks of uterine rupture. The aim of this study was to explore women's decision-making processes and the influences on their mode of birth following a previous CS. Methods A qualitative approach was used. The research comprised three stages. Stage I consisted of naturalistic observation at 33-34 weeks' gestation. Stage II involved interviews with pregnant women at 35-37 weeks' gestation. Stage III consisted of interviews with the same women who were interviewed postnatally, 1 month after birth. The research was conducted in a private medical centre in northern Taiwan. Using a purposive sampling, 21 women and 9 obstetricians were recruited. Data collection involved in-depth interviews, observation and field notes. Constant comparative analysis was employed for data analysis. Results Ensuring the safety of mother and baby was the focus of women's decisions. Women's decisions-making influences included previous birth experience, concern about the risks of vaginal birth, evaluation of mode of birth, current pregnancy situation, information resources and health insurance. In communicating with obstetricians, some women complied with obstetricians' recommendations for repeat caesarean section (RCS) without being informed of alternatives. Others used four step decision-making processes that included searching for information, listening to obstetricians' professional judgement, evaluating alternatives, and making a decision regarding mode of birth. After birth, women reflected on their decisions in three aspects: reflection on birth choices; reflection on factors influencing decisions; and reflection on outcomes of decisions. Conclusions The health and wellbeing of mother and baby were the major concerns for women. In response to the decision-making influences, women's interactions with obstetricians regarding birth choices varied from passive decision-making to shared decision-making. All women have the right to be informed of alternative birthing options. Routine provision of explanations by obstetricians regarding risks associated with alternative birth options, in addition to financial coverage for RCS from National Health Insurance, would assist women's decision-making. Establishment of a website to provide women with reliable information about birthing options may also assist women's decision-making.